THE INFLUENCE OF WORK RECOGNITION, WORK MOTIVATION, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT AMONG INDONESIAN DISTRICT COURT JUDGES - Anang Riyan Ramadianto; Sri Wartini; Euis Soliha; Sandy Arief (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Grounded in Self-Determination Theory and Friedman’s Legal System Theory, this study examines the relationships between work recognition (WR), work motivation (WM), career development (CD), employee engagement (EE), and employee performance (EP) among judges in Indonesian District Courts. In addition, this study investigates the mediating role of employee engagement in the relationships between work recognition, work motivation, career development, and employee performance. A quantitative research approach was employed using a questionnaire survey method. Data were collected from 151 judges working in District Courts across Indonesia through online questionnaires distributed via Google Forms. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The findings revealed that work motivation and career development positively and significantly affect employee performance, whereas work recognition does not have a significant direct effect on employee performance. However, work recognition positively and significantly influences employee engagement. Furthermore, work motivation and career development significantly affect employee engagement, while employee engagement positively and significantly influences employee performance. The mediation analysis also confirmed that employee engagement significantly mediates the relationships between work recognition, work motivation, career development, and employee performance. These findings indicate that organizational support, motivational factors, and career development opportunities are essential in strengthening judges’ engagement, professionalism, and performance within judicial institutions. Therefore, Indonesian District Courts are encouraged to strengthen organizational recognition systems, enhance motivational support, provide sustainable professional development programs, and implement transparent career advancement systems to improve judicial performance and institutional effectiveness.